A Maturity Model for Digital Product Passports: A Design Science Study - Dimitri Petrik; Fabian Dzierzawa; Kirsten Warthmann (IEEE Access)
As part of the Green Deal announced by the European Commission, digital product passports (DPPs) are becoming increasingly important for companies to become more sustainable. DPPs are an emerging concept to structure sustainability-related product data and make it fit for inter-organizational data sharing. As such, DPPs hold promise for closing information gaps in supply chains and production networks, as well as supporting sustainable paradigms, such as the circular economy. As DPPs are intended to make data available for third parties, their launch requires industrial organizations to develop certain information technology (IT) and data management capabilities. In addition, the solution space for implementing DPPs is vast and is still only determined by vague legislation. These factors create uncertainty for companies that need to launch and operate DPPs. Initial research projects indicate an equifinality in the design of DPPs and do not focus on the processes to integrate the data in DPPs and operate them successfully. To assist industrial organizations in this complex endeavor, this study employs design science research to propose a validated maturity model. The model integrates nine technological and organizational maturation paths that industrial organizations can use to become conscious of their current state and improve systematically to launch and operate DPPs successfully. The knowledge base was derived from a multivocal literature review (MLR) and refined in two series of interviews with experts from industrial organizations. Between the two series of interviews, the maturity model was instantiated as a transfer media. The model enables decision-makers and researchers to assess the systematic optimization of technological and organizational maturation paths, turning DPPs into a competitive advantage for more sustainable decisions.